(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This work comprise synthesis five membered heterocyclic compounds type (1,2-azole) form benzidine derivatives, this work is distributed in to three part :- 1- The one part of this study comprise preparation Diazoinum salt by reaction benzidine with NaNO2 in acidic medium to produce A1 compound. 2-The two part of this study comprise preparation new azo compounds for benzidine by give Diazoinum salt which buries by combination reaction with ethyl aceto acetate and acetyl acetone to produce A2 compound. 3-The three part comprise preparation new derivatives of pyrazoline-5-one, pyrazole, isoxazoline -5-one by reaction of compounds in one part with phenyl hydrazine,hydrazine hydrate to produce A3,A4,A5,A6,A7 compounds. This compounds may be have biological activity in addition this can be used for application in oil, fuels and drugs . this compounds was studied and characterized by H1 NMR , IR and C.H.N spectrum , the yield, percentage and boiling point was calculated